High Glucose-Induced Oxidative Stress Mediates Apoptosis and Extracellular Matrix Metabolic Imbalances Possibly via p38 MAPK Activation in Rat Nucleus Pulposus Cells - Xiaofei Cheng; Bin Ni; Feng Zhang; Ying Hu; Jie Zhao (Journal of Diabetes Research)
Objectives. To investigate whether high glucose-induced oxidative stress is implicated in apoptosis of rat nucleus pulposus cells (NPCs) and abnormal expression of critical genes involved in the metabolic balance of extracellular matrix (ECM). Methods. NPCs were cultured with various concentrations of glucose to detect cell viability and apoptosis. Cells cultured with high glucose (25 mM) were untreated or pretreated with N-acetylcysteine or a p38 MAPK inhibitor SB 202190. Reactive oxygen species (ROS) production was evaluated. Activation of p38 MAPK was measured by Western blot. The expression of ECM metabolism-related genes, including type II collagen, aggrecan, SRY-related high-mobility-group box 9 (Sox-9), matrix metalloproteinase 3 (MMP-3), and tissue inhibitor of metalloproteinase 1 (TIMP-1), was analyzed by semiquantitative RT-PCR. Results. High glucose reduced viability of NPCs and induced apoptosis. High glucose resulted in increased ROS generation and p38 MAPK activation. In addition, it negatively regulated the expression of type II collagen, aggrecan, Sox-9, and TIMP-1 and positively regulated MMP-3 expression. These results were changed by pretreatment with N-acetylcysteine or SB 202190. Conclusions. High glucose might promote apoptosis of NPCs, trigger ECM catabolic pathways, and inhibit its anabolic activities, possibly through a p38 MAPK-dependent oxidative stress mechanism.